Increased farmer willingness to pay for quality cassava (Manihot esculenta Crantz) planting materials: Evidence from experimental auctions in Cambodia and Lao PDR - Delaquis, Erik; Slavchevska, Vanya; Almekinders, Conny J. M.; Newby, Jonathan C.; Sareth, Chea; Tanthapone, Chanphasouk; Struik, Paul C. (Springer, 2024)
Varietal turnover is a major mechanism for farmer adaptation to rapidly changing environmental and market conditions. Understanding factors related to varietal turnover is critical for safeguarding food security in the face of increasingly rapid changes to production contexts. Preference elicitation methods like experimental auctions reveal farmers’ willingness to pay (WTP) for seeds with different characteristics. We engaged farmers growing cassava ( Manihot esculenta Crantz) across a wide geographic scope in Cambodia (n = 321, 4 provinces) and Lao PDR (n = 391, 5 provinces) in modified second-price experimental auctions to determine WTP for three cassava seed classes: farmer-produced planting stems of an undescribed variety, farmer-produced planting stems of an elite variety with lower susceptibility to Cassava Mosaic Disease (CMD), and virus-free tested planting stems of the same elite variety. In Lao PDR, mean auction bids for a bundle of 20 planting stems were 0.54, 0.92, and 1.40 USD for farmer, elite, and elite tested stems, while in Cambodia the analogous mean bids were 0.58, 0.77, and 1.16 USD, respectively. A significantly higher WTP associated with elite variety and tested stems in both countries was influenced by both geographic location (province) and individual socioeconomic farmer characteristics. In Lao PDR this included lower WTP of women, higher WTP of ethnic minorities, and, for improved stems, lower WTP of farmers with increased cassava growing experience. In Cambodia fewer socioeconomic variables affected WTP. Our results indicate significant increases in WTP for clean planting materials and new varieties, supporting market-based clean seed approaches as a component of regional control strategies for the CMD epidemic currently threatening a global agri-food value chain.